1996
DOI: 10.1007/bf00028274
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of rotifers in two environments of the upper River Paran� floodplain (MS) - Brazil

Abstract: We evaluate the influence of abiotic and biotic factors on the community structure of rotifers across a regional hydrological cycle in lotic and lentic environments of the upper River Parana Depth, transparency, temperature, pH, electrical conductivity, dissolved oxygen, chlorophyll a and densities of rotifers were measured at two stations in Lake Guarana (littoral and open water regions) and at one station in the River Baia (open water region) Highest densities of rotifers were found at the lake littoral Cano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 14 publications
4
30
0
2
Order By: Relevance
“…Despite the changes caused by the increase in hydrographic levels, these were modest in relation to ecosystems of other floodplains, possibly explained by the meander form of the lake in study. However, some studies of floodplains have attributed the increase in zooplanktonic diversity to an increase in the hydrographic levels (HARDY 1980, KOSTE & ROBERTSON 1983, CORRALES DE JACOBO & FRUTOS 1985, BONECKER et al 1994, BONECKER & LANSAC-TÔHA 1994. Probably, lakes formed from meanders favor the deposit of large amounts of clay, derived from erosion and sedimentation along the banks of the lake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the changes caused by the increase in hydrographic levels, these were modest in relation to ecosystems of other floodplains, possibly explained by the meander form of the lake in study. However, some studies of floodplains have attributed the increase in zooplanktonic diversity to an increase in the hydrographic levels (HARDY 1980, KOSTE & ROBERTSON 1983, CORRALES DE JACOBO & FRUTOS 1985, BONECKER et al 1994, BONECKER & LANSAC-TÔHA 1994. Probably, lakes formed from meanders favor the deposit of large amounts of clay, derived from erosion and sedimentation along the banks of the lake.…”
Section: Discussionmentioning
confidence: 99%
“…They have been studied in Brazil, especially with regard to the composition and ecology of zooplankton: GREEN (1972) in the Pantanal Matogrossense, LANSAC-TÔHA et al (1992, 1993, BONECKER et al (1994), and BONECKER & LANSAC-TÔHA (1996. The zooplanktonic communities that inhabit different environments present in floodplains, show a standard composition and abundance, depending on the physical, chemical and biological conditions of the environment.…”
mentioning
confidence: 99%
“…As a consequence, physical and chemical parameters exhibit strong variations and thus modify the composition of aquatic communities. Several studies report changes in zooplankton community structure related to the physical and chemical characteristics of this system (Bonecker & Lansac-Toha, 1996;Bonecker et al, 1994;José de Paggi, 1978, 1983Martinez & Frutos, 1986;Paggi & José de Paggi, 1990), but they refer mainly to the upper and middle sections of the rivers Paraná and Paraguay. Thus, rivers flowing into the Rio de la Plata estuary are not well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1970s, several studies demonstrated that mesh sizes commonly used to sample crustacean zooplankton (e.g., ≥ 63 µm) underestimate the abundance of rotifers, and recommended mesh sizes ≤ 35 µm for quantitative sampling of rotifers (Likens and Gilbert 1970;Bottrell et al 1976;Ejsmont-Karabin 1978). Despite these recommendations, many studies still report quantitative estimates of rotifer density or biomass based on samples filtered through mesh sizes > 35 µm, including mesh as large as 63 to 80 µm (Bonecker and Lansac-Toha 1996;Ghadouani et al 1998;Shurin 2000;Strecker et al 2004;Geraldes and Boavida 2007). To illustrate the extent of this problem, we used Biological Abstracts BIOSIS to search for articles published from 1999 through 2007 in peer-reviewed journals with the phrase "zooplankton density" in the topic search field.…”
mentioning
confidence: 99%